2012
DOI: 10.1002/adhm.201200248
|View full text |Cite
|
Sign up to set email alerts
|

Purified Graphene Oxide Dispersions Lack In Vitro Cytotoxicity and In Vivo Pathogenicity

Abstract: Prompted by the excitement from the description of single layer graphene, increased attention for potential applications in the biomedical field has been recently placed on graphene oxide (GO). Determination of the opportunities and limitations that GO offers in biomedicine are particularly prone to inaccuracies due to wide variability in the preparation methodologies of GO material in different laboratories, that results in significant variation in the purity of the material and the yield of the oxidation rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
166
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(173 citation statements)
references
References 46 publications
7
166
0
Order By: Relevance
“…The Raman spectral fingerprints obtained for the synthesised GO, OxMWNT and OxNH were comparable to that reported previously in the literature using identical or similar oxidation processes. 15,33 To then monitor degradation, other characterisation techniques were used including visual observation (Fig. 2a) and UV-Vis absorption (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Raman spectral fingerprints obtained for the synthesised GO, OxMWNT and OxNH were comparable to that reported previously in the literature using identical or similar oxidation processes. 15,33 To then monitor degradation, other characterisation techniques were used including visual observation (Fig. 2a) and UV-Vis absorption (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been demonstrated by previous reports in the literature. 15,33 An explanation for the colouration is that during synthesis, the oxidation of the pristine graphite removes carbon atoms from participating in the extensive electron delocalisation present in graphene. This initially opens the band gap of the component graphene in the longer wavelength regions of the visible spectrum as a result of the reduction in electron delocalisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…165 However, purified GO showed no significant cytotoxicity in epithelial lung carcinoma cells up to 100 μg/mL, and no inflammation or granuloma formation (up to 50 μg/animal dose exposure) in vivo. 166 Lammel et al 167 showed that GO has a dose-dependent toxic effect through plasma membrane damage, that is, loss of plasma membrane structural integrity, which was associated with a strong physical interaction of GO with the phospholipid bilayer. Further, they showed that GO could penetrate the plasma membrane, resulting in altered cell morphology and an augmented number of apoptotic cells.…”
Section: In Vitro Toxicity Of Graphene In Eukaryotic Cellsmentioning
confidence: 99%
“…93 Lateral dimensions of GO nano-sheets do not affect drug-loading capacity but could have limitations regarding blood-brain transport, renal clearance, and biodegradation. 94 The success of a GO-based drug delivery vehicle is dependent on three factors. 78 The first is constructing a carrier with an optimal loading capacity.…”
Section: Introductionmentioning
confidence: 99%